Multimodal lung cancer theranostics via manganese phosphate/quercetin particle - Chong Qiu; Fei Xia; Qingchao Tu; Huan Tang; Yinan Liu; Hongda Liu; Chen Wang; HaiLu Yao; Linying Zhong; Yuanfeng Fu; Pengbo Guo; Weiqi Chen; et al. (Molecular Cancer)
Abstract The diagnosis and treatment of non-small cell lung cancer in clinical settings face serious challenges, particularly due to the lack of integration between the two processes, which limit real-time adjustments in treatment plans based on the patient’s condition and drive-up treatment costs. Here, we present a multifunctional pH-sensitive core-shell nanoparticle containing quercetin (QCT), termed AHA@MnP/QCT NPs, designed for the simultaneous diagnosis and treatment of non-small cell lung cancer. Mechanistic studies indicated that QCT and Mn2+ exhibited excellent peroxidase-like (POD-like) activity, catalysing the conversion of endogenous hydrogen peroxide into highly toxic hydroxyl radicals through a Fenton-like reaction, depleting glutathione (GSH), promoting reactive oxygen species (ROS) generation in mitochondria and endoplasmic reticulum, and inducing ferroptosis. Additionally, Mn2+ could activate the cGAS-STING signalling pathway and promote the maturation of dendritic cells and infiltration of activated T cells, thus inducing tumor immunogenic cell death (ICD). Furthermore, it exhibited effective T2-weighted MRI enhancement for tumor imaging, making them valuable for clinical diagnosis. In vitro and in vivo experiments demonstrated that AHA@MnP/QCT NPs enabled non-invasive imaging and tumor treatment, which presented a one-stone-for-two-birds strategy for combining tumor diagnosis and treatment, with broad potential for clinical application in non-small cell lung cancer therapy. Graphical Abstract